Anomalous Enhancement of Seebeck Coefficient in Pr-Based 1-2-20 System with Non-Kramers Doublet Ground States. (18th March 2015) - Machida, Y; Yoshida, T; Ikeura, T; Izawa, K; Nakama, A; Higashinaka, R; Aoki, Y; Sato, H; Sakai, A; Nakatsuji, S; Nagasawa, N; Matsumoto, K; et al.
Abstract: Low-temperature Seebeck coefficient S/T measurements have been performed on Pr-based 1-2-20 system, Pr Tr 2 X 20 ( Tr = Ti, Ta, V, Ir, X = Al, Zn) with non-Kramers doublet ground states. For Pr Tr 2 X 20 with X = Al, we find a large S/T, which amounts to those of heavy fermion metals. By contrast, S/T for PrIr2 Zn20 is found to be considerably small as the same order of magnitude as those of ordinary metals, despite the commonly enhanced Sommerfeld coefficient γ throughout the system. A satisfactory of the quasi-universal relation between S/T and γ as well as the Kadowaki-Woods relation demonstrates that the mass enhancement is realized in Pr Tr 2 Al20 due to the hybridization between f -electrons and the conduction electrons. We also find that the small S/T of PrIr2 Zn20 is enhanced at low temperatures under the fields on the verge of quadrupole ordered phase, and in the same regime, the electrical resistivity follows the quadratic temperature dependence with a steep slope as a characteristic of Fermi liquid. The results imply an emergence of a nontrivial coherent state with sizable mass enhancement associated with the quadrupole degree of freedom.